Upaya Kepala Sekolah dalam Meningkatkan Kreatifitas Tenaga Pendidik di MA Ar Rahman Sumoyono Diwek Jombang - Arif Rahman Hakim; Sahrun Sahrun (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2018)
The role of the principal is very important, a principal must be able to plan and implement work programs, and conduct regular evaluations of the educational process. Learning is essentially a process of interaction between students and their environment, and emphasizes practice. Religious education in schools has an important role in fostering the generation of the Indonesian nation, both in creating humans with moral values ??and having a high spiritual level. The results of this study: 1) The school principal always monitors the teaching staff in carrying out the tasks that have been provided to be implemented according to their fields, the school principal also always provides motivation to the teaching staff at every opportunity and always supports the teaching staff who want to improve their abilities and creativity by trying fulfill what is needed to support the abilities and creativity of the teaching staff under the auspices of the institution they lead. In addition to motivating the teaching staff of the school principal, he also seeks to meet the needs of the teaching staff in order to increase their creativity. 2) The principal in improving the creativity of educators is to see and monitor the learning process directly, involving all parties in the task, involving educators to attend training that can improve their abilities and creativity.